PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS MULTIMODALITAS PADA MATERI PERUBAHAN WUJUD BENDA KELAS V SEKOLAH DASAR - Maghfiroh, Sindy; Irianto, Dede Margo; Aljamaliah, S. Nailul Muna (JS (JURNAL SEKOLAH), 2023)
Abstract: The rapid development of technology in the era of revolution 4.0 requires the field of education to create innovations, especially in the use of learning media that utilize digital technology. The development of multimodality-based interactive learning media can be used as a variation of the use of innovative digital learning media that can actively involve students in learning to create meaningful learning, one of which is in science learning on the material of changing the form of objects in grade V elementary schools. This research uses the Design and Development (D&D) method with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) procedure. Data collection techniques are carried out through interviews, judgment experts, and questionnaires involving material expert validators, media experts, and linguists to assess the feasibility of interactive learning media as well as teachers and grade V students as users of interactive media. Due diligence results obtained from material experts 94% (Very Feasible), media experts 90.5% (Very Feasible), and linguists 78.85% (Eligible). In the trial phase, the percentage of teacher response was 79.54% (Feasible) and student response was 92.05% (Very Feasible). Based on the results of the assessment by expert validators and user responses, it can be concluded that interactive learning media based on multimodality is suitable for use in the learning process. Keyword: Design and Development Research, Learning Media, Interactive Media, ObjectTransformation. Abstrak: Perkembangan teknologi yang terjadi sangat pesat pada era revolusi 4.0 menuntut bidang pendidikan untuk menciptakan inovasi terutama dalam penggunaan media pembelajaran yang memanfaatkan teknologi digital. Pengembangan media pembelajaran interaktif berbasis multimodalitas dapat dijadikan salah satu variasi penggunaan media pembelajaran digital yang inovatif yang dapat melibatkan siswa secara aktif dalam pembelajaran sehingga dapat menciptakan pembelajaran yang bermakna, salah satunya dalam pembelajaran IPA pada materi perubahan wujud benda kelas V sekolah dasar. Penelitian ini menggunakan metode Design and Development (D&D) dengan prosedur ADDIE (Analysis, Design, Development, Implementation, Evaluation). Teknik pengumpulan data dilakukan melalui wawancara, judgement expert, dan angket yang melibatkan validator ahli materi, ahli media, dan ahli bahasa untuk menilai kelayakan media pembelajaran interaktif serta guru dan siswa kelas V sebagai pengguna media interaktif. Hasil uji kelayakan yang diperoleh dari ahli materi 94% (Sangat Layak), ahli media 90,5% (Sangat Layak), dan ahli bahasa 78,85% (Layak). Pada tahap uji coba diperoleh persentase respon guru 79,54% (Layak) dan respon siswa 92,05% (Sangat Layak). Berdasarkan hasil penilaian oleh validator ahli dan respon pengguna, maka dapat disimpulkan bahwa media pembelajaran interaktif berbasis multimodalitas layak untuk digunakan dalam proses pembelajaran.Kata Kunci: Penelitian Desain dan Pengembangan, Media Pembelajaran, Media Interaktif, Perubahan Wujud Benda.